Análisis musicológico post mortem: Colombo a Santo Domingo o la ópera del Centenario - Gómez Rivas, Armando (El Colegio de México, A.C., 2021)
In 1892, the celebrations for the quatercentenary of the discovery of America included the participation of musicians. The climax of these festivities was the premiere of Colombo a Santo Domingo by the Mexican composer Julio Morales. The nature of this piece implied that Mexico would contribute, with its own voice, to the most aristocratic genre in music: opera. Nevertheless, after the premiere and one benefit performance immediately afterwards, Colombo a Santo Domingo was immediately withdrawn by its composer and it was never performed again. Morales himself wondered if the absence of a critical response was a sign of the piece’s true aesthetic achievements.This article questions the process that led him to withdraw the piece from the centennial opera season by studying the programming of the Italian Opera Company run by the businessman Napoleón Sieni. By viewing this piece in the context of the other operas presented that season, it puts forward a hypothesis based on a comparison between the Mexican opera and the classics of the bel canto canon.This argument is supported through an analysis of the contemporary press. As part of a historiographic process, it proposes a critique of the musical criticism of the time, allowing us to better understand the opera’s reception. It concludes with a musical analysis of Morales’s own score.